ANALISIS PENGELOLAAN CABANG BANK; DARI MANA BANK MERAIH PROFIT ? - Iman Sidik Nusannas (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2017)
Banking management, as also enterprise management is always an interested topic to discuss, since the goal of bank as also enterprise is to reach the profit. Profit can be gained from three main bank activities ie; Funding Lending and services. Three acvtities will earn profit with a proper manner to manage. From lending and Funding a bank can gain spread based income and from services bank can gain fee based income.This journal is to look up those three bank activities. Keywords: Bank, Funding, Lending, Services.